Effect of pre-ICU aspirin use on neuroinflammation and outcomes in patients with sepsis-associated encephalopathy - Xu, Zhenkun; Yang, Qichao; Li, Hunian; He, Ting (Frontiers in Neurology, 2026)
ObjectiveTo investigate the effect of pre-ICU aspirin use on neuroinflammation and prognosis in sepsis-associated encephalopathy (SAE) patients.MethodsClinical data of SAE patients admitted to our ICU (Mar 2022–Feb 2025) were retrospectively analyzed. Patients were grouped based on pre-admission aspirin use: exposed (n = 45) and non-exposed (n = 68). After 1:1 propensity score matching (age, infection source; caliper = 0.2), 42 matched pairs were compared. Cerebral hemodynamics (Vm, Vd, and Vs), coagulation function (PLT, TT, PT, and APTT), neuroinflammation markers (IL-6, TNF-α, and S100β), Glasgow Coma Scale (GCS), Sequential Organ Failure Assessment (SOFA) scores (admission, days 1, 3, and 5), ICU length of stay, adverse events, 28- and 60-day mortality were analyzed using appropriate statistical tests (t-test, χ2 test; P < 0.05 significant).ResultsThe exposed group had higher Vm, Vd, and Vs at all time points (P < 0.05). IL-6, TNF-α, and S100β levels were lower in the exposed group (P < 0.05). GCS scores were higher in the exposed group on days 3 and 5 (P < 0.05). Adverse event incidence, ICU stay, and 28-day mortality did not differ significantly (P < 0.05). The 60-day mortality was lower in the exposed group (P < 0.05).ConclusionsPre-ICU aspirin use can improve cerebral hemodynamics, reduce neuroinflammation, and improve 60-day survival in SAE patients without increasing adverse reactions.